Ethnobotanical Study Of the Zingiberaceae Family in Local Community Life in Padang Bubus Village, Bonjol District, Pasaman Regency, West Sumatera. - Rahmi Hidayah Putri _ (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2023)
Abstract The community of Padang Bubus is a local community that lives in the hills, Bonjol Subdistrict, Pasaman Regency. The plant utilization knowledge has been inherent in their societal culture as medicine, food, building materials and as also ritual material. The deterioration in tranditional treatment knowledge for younger generations is feared by loss of information regarding the utilization of herbs as medicine. This research aimed to investigate the use of Zingiberaceae for traditional medicine in Padang Bubus Village, Bonjol Subdistrict, Pasaman Regency. This research had been carried out from Januari to Februari 2023. The result showed that 8 Zingiberaceae species used by local people in Padang Bubus village were Curcuma domestica, Curcuma xanthorrizha, Costus spesiosus, Alpinia galanga, Kaemferia galanga, Zingiber officinale, Etlingera elatior and Amomum compactum. Botanical studies show that this family is more dominant in herbaceous stature with pseudo stems and can be distinguished between species by the color of the rhizomes. Ethnomedicine studies show that this family is more likely to treat internal medicine. Ethnoecological studies show that this family has been widely cultivated rather than wild, but has not been tested as a natural herbicide and pesticide. Keyword : Ethnobotany, Padang Bubus, ethnomedicine, ethnoecology, Zingiberaceae.